Comparison of the cloned H-2Kbm1 variant gene with the H-2Kb gene shows a cluster of seven nucleotide differences. - Schulze, D H (1983)
The gene for the H-2K class I antigen of the bm1 variant was cloned and analyzed at the DNA level and compared with the previously cloned parent B6/Kh gene. Sequence determination and comparative restriction endonuclease studies indicate that Kbm1 is derived from the Kb gene. Seven nucleotide changes within a 13-nucleotide stretch distinguish the mutant from the parent gene and result in amino acid differences at positions 152, 155, and 156 in the antigen. The data confirm previously reported changes at amino acid positions 155 and 156 (arginine to tyrosine and leucine to tyrosine, respectively) and extend the altered region to include two nucleotides encoding a glutamate to alanine substitution at amino acid 152, a change not detected by the protein studies because of limitations of the methods used. The DNA sequence encoding this region of the Kbm1 glycoprotein is identical to the DNA sequence of at least one other known class I gene in the mouse, a finding consistent with the hypothesis that the mutation was not a random event but may be the result of a block transfer of information by a copy mechanism analogous to gene conversion. As the sequence analysis of the coding region for the first 273 amino acid residues shows identity between parent and mutant except for the seven nucleotide changes, all variant-parent functional differences must depend only on the cluster of three amino acid differences in the second domain of the Kb glycoprotein.